Nutraceutical rice bran oil manufacturing plant using supercritical carbon dioxide extraction process a plant design - Abad, Jonabel F.; Rebong, Judy Ann V.; Revereza, April Joy R.
Rice bran oil is considered to be superior to the traditional cooking oil and was proven to be an effective nutraceutical oil. The raw material for it production is rice bran, a by product from rice milling. The qualities of rice bran oil are much better as compared to other vegetable oils in the market, especially in terms of the health benefits that is could offer. Rice bran oil has a very high smoke point which makes it perfect for deep frying and the best choice in replacing hydrogenated oil containing trans fatty acids.The Philippines is one of the top countries that produces rice. Therefore, there is no doubt that the raw material of the product can maintain the production of the plant. From the market data and analysis, the feasibility of the proposed plant is defined. The analysis was based on the supply and demand of the raw material, the market trends, the competitors of the product, and the projection of the local production.The object of this study is to put up a rice bran oil processing plant that would open the potential of rice bran as a nutraceutical vegetable oil in the Philippines. The proponents also considered the quality of the oil, the processes that were selected are of premium efficiency. The general design consideration are also presented in the study as well as the mass of energy balances that defines the ocst that the plant would incur.The location of the plant was surveyed to be in Nueva Ecija due to the abundance of rice millers and the cheaper cost of land properties in the area. The location also provides ease of transport since it is about 2 hours away from Metro Manila. The processes involved in the study include the stabilization of the rice bran, extraction of the oil through supercritical fluid extraction, and the refining of the extracted oil. The advantage of this proposed method is in the amount of the nutraceutical components present in the final product. The major equipment involved in the study include: dryer, extraction unit, bleaching system, and the deodorization system. The design of these equipment and other minor ones are also presented in the study as well as a Hazard and Operability Study that defines the process controls required for each equipment operations. A piping system that detailed plant layout are also included as well as a waste management analysis.Based from economic feasibility studies and mass and energy balance calculations, the rate of production of the said plant is around 30,000 kg per day. This would equal to a total product cost of Php 2,087,535,864.91, an annual revenue of Php 6,232,977,642.87, and a gross income after tax of Php 3,043,851,378.97, and. The production is calculated to be sold at an amount of Php 200 per liter. The proposed plant would have a Rate of Return of 38.64% and a 3.23-year payback period.